PENGARUH WORK LIFE BALANCE DAN QUALITY OF WORK LIFE TERHADAP WORKENGAGEMENT PADA GENERASI DI KOTA BEKASI - Sendy Wijaya; Tyna Yunita, Jumawan (BORJUIS: JURNAL OF ECONOMY, 2024)
The Influence of Work life balance and Quality of work life on Work engagement in Generation Z in the city of Bekasi. This research aims to find out whether Work life balance can influence Generation Z's Work engagement through Quality of Work Life. This research method is quantitative, the sampling technique is Accidental Sampling. This research uses an instrument in the form of a questionnaire which has been compiled into several statements and measured using a Likert scale. The population used in this research is generation Z in the city of Bekasi. This research uses Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach and uses SmartPLS 4.0 software to analyze the data. Based on the research results: 1) Work life balance in this study shows that there is a significant influence on Work engagement, 2) Quality of work life in this study shows that there is a significant influence on Work engagement, 3) Work life balance in this study shows that there is significant influence on Quality of work life and 4) Quality of work life in this study was proven to be significant and was stated as Partial Mediation